2022
DOI: 10.1038/s41467-022-31355-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of molecular characteristics in Burkitt lymphoma differs according to age

Abstract: While survival has improved for Burkitt lymphoma patients, potential differences in outcome between pediatric and adult patients remain unclear. In both age groups, survival remains poor at relapse. Therefore, we conducted a comparative study in a large pediatric cohort, including 191 cases and 97 samples from adults. While TP53 and CCND3 mutation frequencies are not age related, samples from pediatric patients showed a higher frequency of mutations in ID3, DDX3X, ARID1A and SMARCA4, while several genes such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…For instance, the reasons for the differences in clinical outcome between pediatric and adult BL patients after initial therapy and poor survival rates at relapse on both pediatric and adult BL remain poorly understood. A recent clinical study comparing adult and pediatric cohorts showed that mutations in the BCL2 and YY1AP1 genes are characteristic of adult patients, while mutations in ID3, DDX3X, ARID1A and SMARCA4 are more frequent in pediatric patients (123). The DDX3X gene is one of the most frequently mutated in c-MYC translocated pediatric BL after TP53, ID3 and TCF3 in this study (122)(123)(124)(125), but also in others.…”
Section: Ddx3x Mutations In Burkitt Lymphoma and Diffuse Large B-cell...supporting
confidence: 54%
See 3 more Smart Citations
“…For instance, the reasons for the differences in clinical outcome between pediatric and adult BL patients after initial therapy and poor survival rates at relapse on both pediatric and adult BL remain poorly understood. A recent clinical study comparing adult and pediatric cohorts showed that mutations in the BCL2 and YY1AP1 genes are characteristic of adult patients, while mutations in ID3, DDX3X, ARID1A and SMARCA4 are more frequent in pediatric patients (123). The DDX3X gene is one of the most frequently mutated in c-MYC translocated pediatric BL after TP53, ID3 and TCF3 in this study (122)(123)(124)(125), but also in others.…”
Section: Ddx3x Mutations In Burkitt Lymphoma and Diffuse Large B-cell...supporting
confidence: 54%
“…A recent clinical study comparing adult and pediatric cohorts showed that mutations in the BCL2 and YY1AP1 genes are characteristic of adult patients, while mutations in ID3, DDX3X, ARID1A and SMARCA4 are more frequent in pediatric patients (123). The DDX3X gene is one of the most frequently mutated in c-MYC translocated pediatric BL after TP53, ID3 and TCF3 in this study (122)(123)(124)(125), but also in others. While the role and mechanistic consequences of loss-of-function (LOF) mutations in TP53, ID3 and TCF3 have been clarified to a large part, it remains unclear why mutation in the DDX3X gene are selected in BL and the question remains whether this protein is indeed a tumor suppressor or not, or whether it exerts both roles in a context-dependent manner (126).…”
Section: Ddx3x Mutations In Burkitt Lymphoma and Diffuse Large B-cell...supporting
confidence: 54%
See 2 more Smart Citations
“…Intriguingly, recent studies indicate age-dependent mutation patterns for ARID1A. In Burkitt lymphoma, in contrast to TP53 and CCND3, mutation frequencies of which are not age related, samples from pediatric patients showed a higher frequency of mutations in ARID1A than those from adults [ 32 ]. Similarly, comparison of younger to older women with luminal A tumors revealed significant differences in somatic alterations in three prevalent driver genes.…”
Section: Arid1a: Context-dependent Functionsmentioning
confidence: 99%